2018
DOI: 10.1021/acs.jpcc.7b10902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TiO2 in Low Temperature Propylene Epoxidation Using Gold Catalysts

Abstract: Propylene epoxidation with molecular oxygen has been proposed as a green and alternative process to produce propylene oxide (PO). In order to develop catalysts with high selectivity, high conversion, and long stability for the direct propylene epoxidation with molecular oxygen, understanding of catalyst structure and reactivity relationships is needed. Here, we combined atomic layer deposition and deposition precipitation to synthesize series of well-defined Au-based catalysts to study the catalyst structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…According to Figure 10, it is the OOH species formed on Au nanoparticles that directly transfers to the neighboring Ti sites (interfacial Ti sites at the dual Au/Ti sites) to form active Ti-OOH species and epoxidize propylene to form an oxametallacycle OMP (OMC' or OMC", depending on which carbon of propylene is connected with O). Their KMC simulations closely reproduce the experimental findings [140]. For instance, it was found that the O 2 feed concentration has a slight effect on PO selectivity (since O 2 adsorption on Au particles is very weak), which is in good agreement with the kinetic tests of Taylor and Chen [142,143].…”
Section: Reaction Mechanism On Au/ti Interface Sitessupporting
confidence: 75%
See 1 more Smart Citation
“…According to Figure 10, it is the OOH species formed on Au nanoparticles that directly transfers to the neighboring Ti sites (interfacial Ti sites at the dual Au/Ti sites) to form active Ti-OOH species and epoxidize propylene to form an oxametallacycle OMP (OMC' or OMC", depending on which carbon of propylene is connected with O). Their KMC simulations closely reproduce the experimental findings [140]. For instance, it was found that the O 2 feed concentration has a slight effect on PO selectivity (since O 2 adsorption on Au particles is very weak), which is in good agreement with the kinetic tests of Taylor and Chen [142,143].…”
Section: Reaction Mechanism On Au/ti Interface Sitessupporting
confidence: 75%
“…In their model, H 2 O 2 is first generated from coadsorbed H 2 and O 2 on Au nanoparticles, and H 2 O 2 can then either degrade into water or diffuse to TiO 2 sites supported on SiO 2 to epoxidize propylene molecules [139]. The PO formation rates predicted by KMC simulations are consistent with experimental reports corresponding to different temperatures and feed concentrations of O 2 [140]. In their later kinetic modeling studies [141], several key side reactions encountered during PO formation are taken into account (acrolein formation, propanal and acetone formation from OMP isomerization, oxidative cracking into CO 2 , etc.…”
Section: Reaction Mechanism On Au/ti Interface Sitessupporting
confidence: 73%
“…It is well known that small Au nanoparticles, and particularly those with a core diameter below 5 nm, are crucial to achieve catalytic activity in propylene epoxidation. [ 7a , 22 ] Thus, in an effort to avoid harsh ligand removal methods, we demonstrate a simple way to remove ligands by using a non‐thermal O 2 plasma technique that does not induce an increase in the size of the Au nanoparticles. [23] Figure 2 d schematically illustrates the O 2 plasma removal procedure for Au/TS‐1 materials.…”
Section: Resultsmentioning
confidence: 99%
“…This makes it very difficult to control catalytic activity through a specific particle size. It is well known that small Au nanoparticles, and particularly those with a core diameter below 5 nm, are crucial to achieve catalytic activity in propylene epoxidation [7a, 22] . Thus, in an effort to avoid harsh ligand removal methods, we demonstrate a simple way to remove ligands by using a non‐thermal O 2 plasma technique that does not induce an increase in the size of the Au nanoparticles [23] .…”
Section: Resultsmentioning
confidence: 99%